Effects of ascorbic acid and DL-alpha-tocopherol on human hepatoma cell proliferation and redifferentiation - Kang Jiu-Hong; Shi Yi-Min; Zheng Rong-Liang (Acta Pharmacologica Sinica, 2016)
"AIM: To examine the effects of ascorbic acid (AA) and DL-alpha-tocopherol (alpha T) on the proliferation and redifferentiation of human hepatoma cell. METHODS: Choosing an all-trans retinoic acid (RA) as a positive control, cell surface charge, biochemical changes, and cell growth in soft agar were measured. RESULTS: After treatment with AA 4 mmol.L-1 and alpha T 1 mmol.L-1 together, the growth curve and mitotic index of human hepatoma cells decreased remarkably, the cellular growth inhibitory rate amounted to 61.3%. The indices related to cell malignancy alleviated significantly; cell surface charge decreased, the electrophoresis rate dropped from 1.64 to 0.89 microns.s-1.V-1.cm-1, the average value of alpha-fetoprotein (alpha-FP) content decreased from 300 to 80 micrograms.g-1 (protein), and gamma-glutamyl-transpeptidase (gamma-GT) activity decreased from 0.81 to 0.201 U.g-1(protein). The index related to cell differentiation increased significantly, such as the average level of tyrosine-alpha-ketoglutarate transaminase activity increased from 10.6 to 45 micrograms.g-1 (protein), and the colonogenic potential decreased by 96.6%. CONCLUSION: AA and alpha T combination inhibited human hepatoma cell proliferation, induced redifferentiation, and reversed its malignant phenotypic characteristics."